Exercise-based strategies to prevent muscle injury in male elite footballers: an expert-led delphi survey of 21 practitioners belonging to 18 teams from the Big-5 European Leagues - McCall, A.; Pruna, R.; Van der Horst, N.; Dupont, G.; Buchheit, M.; Coutts, A. J.; Impellizzeri, F. M.; Fanchini, M. (Sports Medicine, 2020)
Purpose: To define based on expert opinion and practical experience using a systematic and scientific approach, (1) the perceived most effective exercise-based strategies to prevent muscle injury in elite footballers; and, (2) when and how these exercise programs are prescribed based on the number of days between games i.e. implementation strategy. Methods: A Delphi survey obtained opinions and assessed for agreement. Delphi respondents consisted of 21 experienced sports practitioners (12 ± 5.3 years in elite football and with an academic background) belonging to 18 teams from the Big-5 European football leagues; England, France, Germany, Italy, Spain. Three teams were represented collaboratively by two experts. The Delphi process involves sequential rounds each evolving based on the responses from the previous. The number of rounds is not pre-defined and continues until an agreement is either achieved or it is clear that no agreement will be reached. Frequency of responses was recorded where the agreement was sought (i.e. in closed questions) and an agreement was achieved if >= 13/18 (70%) respondents agreed. For open-ended questions, a qualitative content analysis was performed to identify recurring themes and when themes were specified by >= 13 (70%), these were also considered as reaching an agreement. Practitioners had the opportunity to raise concerns if they disagreed with the `agreement from recurrent themes`. Results: There were four Delphi rounds (100% response for each round). Sprinting and High-Speed Running (HSR) focused exercises were agreed as most effective (perceived) to prevent muscle injuries. Eccentric exercise was perceived as the next most effective. It was agreed that sprinting and HSR be integrated into coaches training, and target 100% of players worst-case match scenario (e.g. volume, intensity) based on individual maximum speeds. Eccentric exercise was recommended to be implemented according to the context of the main football session and planned/actual sprinting and HSR content. It was agreed that eccentrics can be performed before or after training, context dependent. The day to perform specific sprinting and HSR or eccentric exercises depended on the proximity of previous and upcoming matches. Other exercises reaching agreement as `somewhat effective` included concentric and isometric, horizontal and vertical plyometrics, coordination, core and dynamic flexibility in addition to core stability. No agreement was reached for multi-joint, resisted sprinting, kicking or agility exercises nor simultaneous single-leg strength and stability. Finally, no agreement was reached regarding programming variables e.g. sets, repetitions as deemed too contextual. Conclusion: Regarding exercise-based strategies, particular importance agreed by the Delphi expert group was to focus on sprinting, HSR and eccentric exercises, integrated with a variety of other exercise modes which also carry some level of effectiveness in a multidimensional programme. Context was agreed to be key and decision-making about when to undertake/ how to prescribe exercise strategies to be made according to the content of normal football training and the proximity of matches.